Effectiveness of Lawsonia Inermis for Psychopharmacological Activity on Staircase in Nmri Mice (Medical Forum Monthly, 2024)
Objective: To evaluate the psychopharmacological activity of methanolic extract of Lawsonia inermis (Meli) in Albino mice.Study Design: Observational studyPlace and Duration of Study: This study was conducted at the Department of Pharmacology, Faculty of Pharmacy, Hamdard University, Karachi from January, 2014 to June, 2014.Materials and Methods: The study was approved by the ethical review committee of the institute. Lawsonia inermis leaves were gathered from the botanical greenery enclosure of the Hamdard University premises their pharmacognostic details were authenticated from Eastern Medication Faculty of Hamdard University, Karachi. Albino mice (30-35g) of either sex were gotten from the creature place of Dr. HMI Institute of Pharmacy and Herbal Sciences, Hamdard University, Karachi. Psychopharmacological activity was studied by utilizing stair case test which is normally utilized as a part of rat for hostile to tension like conduct that is based comprises of setting local queasiness in an encased box with 5 steps.Absolutely thirty six (N=36) were arbitrarily partitioned into six sets. For each of the model considered (n=6). The groups incorporate controls (vehicle) and standard medications (Diazepam, Buspirone, 1mg/kg) and three groups of Meli (50, 100 and 200 mg/kg).Results: Meli dosage of 100mg/kg drastically (P<0.05, 0.01) augmented the number of steps up in the Stair case with peak activity procured at the dosage of 100mg/kg (37.8±4.2) seconds compared to control (6.3±2.2 Seconds). The extract at dosage of 100mg/kg notably (P<0.05, 0.01) accelerated the number of steps up with peak effect at the dosage of 100mg/kg (37.8±4.2) compared to control (6.3±2.2 seconds). The impact at this measurement was not quite different that of Diazepam (41.8±3.4 seconds).Conclusion: Meli has explored anxiolytic effect because it possesses one or a mix of Phytoconstituents in the concentrate.